Zinc oxide nanoparticles and application thereof
By using the core-shell structure of zinc oxide nanoparticles in sunscreen to control their particle size and charge, the problems of weakening the effects of traditional sunscreens and generating reactive oxygen species are solved, and stronger ultraviolet absorption and better use comfort are achieved. .
Patent Information
- Application Number
- CN202411851593.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The effect of sunscreen chemical reagents in traditional sunscreens is weakened under the action of ultraviolet rays and may irritate or damage the skin. Nano zinc oxide produces reactive oxygen species under ultraviolet light excitation, affecting sun protection performance.
The core-shell structure of zinc oxide nanoparticles is adopted, where the core core is carboxylated modified silica and the shell layer is zinc oxide. The average hydrated particle size, polydispersion index and Zeta potential of the nanoparticles are controlled by a specific preparation method. Reduce singlet oxygen generation under ultraviolet excitation.
It improves the ultraviolet absorption capacity of sunscreen, reduces the production of reactive oxygen species, enhances sunscreen performance and comfort, reduces dependence on thickeners, and is suitable for skin types in more people.
Smart Images

Figure CN119302860A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sunscreen, and in particular to zinc oxide nanoparticles and applications thereof. Background Art
[0002] Due to the effects of ultraviolet (UV) rays in sunlight, the incidence of melanoma skin cancer has increased significantly and is the most common cancer among people aged 25 to 29. It is recommended to use sunscreen to prevent skin cancer, sunburn, photoaging and skin wrinkles. It is generally known that ultraviolet rays can be divided into several bands, namely UVA, UVB, UVC and UVD, according to different wavelengths. Among them, UVA and UVB are the two bands most relevant to human health.
[0003] The wavelength of UVA radiation is 320-400nm. Such UVA radiation can burn the skin, and overexposure may cause skin cancer. The wavelength of UVB radiation is 280-320nm, which may cause short-term or long-term skin damage, including the formation of deep wrinkles, collagen breakage and spot pigmentation. From the 22nd World Federation of Cosmetic Chemist Associations Symposium (Edinburgh 2002, Oral Papers, Vol.2, Zastrow et al.) conference publications and other publications, it can be seen that by electron spin resonance (ESR) imaging, it has been determined that UVA and UVB rays can penetrate to different depths of the skin, UVB rays can penetrate up to a depth of about 50μm, and UVA radiation can reach the dermis below, i.e. about 3mm. Therefore, sunscreen plays an important role in daily UV protection.
[0004] The sunscreen chemicals contained in traditional sunscreens absorb ultraviolet rays and then decompose to reduce the ultraviolet rays. Therefore, as the exposure time increases, the effect continues to weaken and needs to be repeatedly used. In addition, some sunscreen chemicals or chemicals produced by decomposition may irritate or damage the skin. Nano zinc oxide (ZnO) is a broad-spectrum inorganic ultraviolet shielding agent. It is increasingly widely used because it shields ultraviolet rays by physical means. The principle of shielding ultraviolet rays is to absorb and scatter ultraviolet rays. When exposed to ultraviolet rays, electrons in the valence band can absorb ultraviolet rays and be excited to the conduction band, and hole-electron pairs are generated at the same time, so it has the function of absorbing ultraviolet rays. However, the scattering of ultraviolet rays by nano ZnO conforms to Rayleigh scattering. When the particle size is much smaller than the wavelength of ultraviolet rays, nanoparticles can scatter the ultraviolet rays acting on them in all directions, thereby reducing the intensity of ultraviolet rays in the irradiation direction. Such descriptions are recorded in CN105030571B.
[0005] In order to solve this problem, Yan Chunyue et al. published a paper titled ZnO@SiO 2The application and testing of sunscreen agents described that the surface of nano ZnO is coated with SiO 2 Preparation of ZnO@SiO 2 Composite materials. SiO 2 It is inert and can inhibit the photocatalytic activity of nano ZnO. 2 The shell layer can increase the transparency of ZnO in the visible light region. However, the article also points out that due to the outer SiO 2 The shielding effect of the shell on ZnO leads to a decrease in its sunscreen performance. CN116171146A (the corresponding commercial product is Pavise) discloses a nanoparticle with a nanodiamond as the core and zinc oxide or titanium oxide as the shell. The nanodiamond core removes holes through an internal oxidation process or by capturing electrons in the conduction band of the shell. However, nanodiamonds are expensive and difficult to prepare. Summary of the invention
[0006] The present invention provides a zinc oxide nanoparticle, wherein the outer layer of the nanoparticle is zinc oxide; when the nanoparticle is dispersed in water, the average hydrated particle size is ≤90nm, Average hydrated particle size / (TEMa+TEMb)≤1, TEMa and TEMb represent the minimum and maximum TEM particle sizes, respectively; Or, the outer layer of the nanoparticles is zinc oxide; When the nanoparticles are dispersed in water, the average hydrated particle size is ≤90nm; When the concentration of the nanoparticles dispersed in water is 0.2 mg / ml, the generation of singlet oxygen is no more than 16% under ultraviolet light excitation for 10 s.
[0007] Preferably, the nanoparticles are of a core-shell structure, wherein the core is silicon dioxide and the shell is zinc oxide. Preferably, the silicon dioxide is carboxyl-modified silicon dioxide.
[0008] When the nanoparticles are dispersed in water, the average hydrated particle size of the zinc oxide nanoparticles is ≤90nm; preferably, 50nm≤average hydrated particle size≤90nm, or 60nm≤average hydrated particle size≤90nm, or 70nm≤average hydrated particle size≤90nm, or 60nm≤average hydrated particle size≤85nm.
[0009] When the nanoparticles are dispersed in water, the PDI of the zinc oxide nanoparticles is ≤0.3, preferably, PDI ≤0.2, or PDI ≤0.19, or PDI ≤0.18, or PDI ≤0.17.
[0010] When the nanoparticles are dispersed in water, the Span of the zinc oxide nanoparticles is ≤1.5, or ≤1.4, or ≤1.3, or ≤1.2, or ≤1.1, or ≤1.0, or ≤0.9, or ≤0.8, or ≤0.7. Preferably, 0.1≤Span≤1.5, or 0.2≤Span≤1.4, or 0.3≤Span≤1.3, or 0.4≤Span≤1.2, or 0.5≤Span≤1.1, or 0.5≤Span≤1.0, or 0.5≤Span≤0.9, or 0.5≤Span≤0.8, or 0.5≤Span≤0.7.
[0011] When the nanoparticles are dispersed in water, the D10 of the zinc oxide nanoparticles is ≤60 nm. Preferably, 20 nm ≤ D10 ≤ 60 nm, or 21 nm ≤ D10 ≤ 60 nm, or 22 nm ≤ D10 ≤ 60 nm, or 23 nm ≤ D10 ≤ 60 nm, or 24 nm ≤ D10 ≤ 60 nm, or 25 nm ≤ D10 ≤ 60 nm, or 30 nm ≤ D10 ≤ 60 nm, or 40 nm ≤ D10 ≤ 60 nm, or 45 nm ≤ D10 ≤ 55 nm.
[0012] When the nanoparticles are dispersed in water, the zinc oxide nanoparticles have a D50≤80nm. Preferably, D50≤79nm, or D50≤78nm, or D50≤77nm, or D50≤76nm, or D50≤75nm, or 30nm≤D50≤80nm, or 35nm≤D50≤80nm, or 40nm≤D50≤80nm, or 45nm≤D50≤80nm, or 50nm≤D50≤80nm, or 55nm≤D50≤80nm, or 60nm≤D50≤80nm, or 65nm≤D50≤80nm.
[0013] When the nanoparticles are dispersed in water, the zinc oxide nanoparticles have a D90 of ≤110 nm. Preferably, D90 ≤109 nm, or D90 ≤108 nm, or D90 ≤107 nm, or D90 ≤106 nm, or D90 ≤105 nm, or D90 ≤104 nm, or D90 ≤103 nm, or D90 ≤102 nm, or D90 ≤101 nm, or D90 ≤100 nm, or 50 nm ≤ D90 ≤105 nm, or 60 nm ≤ D90 ≤105 nm, or 70 nm ≤ D90 ≤105 nm, or 80 nm ≤ D90 ≤105 nm, or 80 nm ≤ D90 ≤100 nm, or 80 nm ≤ D90 ≤90 nm.
[0014] When the nanoparticles are dispersed in water, the absolute value of the Zeta potential of the zinc oxide nanoparticles is ≥15mV, or ≥16mV, or ≥17mV, or ≥18mV, or ≥19mV, or ≥20mV, or ≥21mV, or ≥22mV, or ≥23mV, or ≥24mV, or ≥25mV. When the nanoparticles are dispersed in water, preferably, the Zeta potential is 18-40mV, or 19-40mV, or 18-35mV, or 19-35mV, or 18-34mV, or 19-34mV.
[0015] When the nanoparticles are dispersed in water, the TEM particle size of the zinc oxide nanoparticles is 30-70 nm, or the TEM particle size is 30-80 nm.
[0016] When the nanoparticles are dispersed in water, the average hydrated particle size of the zinc oxide nanoparticles / (TEM a +TEM b )≤1, TEMa and TEMb represent the minimum and maximum TEM particle sizes, respectively. Preferably, the average hydrated particle size / (TEM a +TEM b )≤0.9, or ≤0.8, or ≤0.7. Preferably, the average hydrated particle size of the zinc oxide nanoparticles / (TEM a +TEM b )≤0.8,60nm≤average hydrated particle size≤85nm.
[0017] The inventors of the present invention unexpectedly discovered that while pure nano ZnO materials can protect against the sun, they can also be stimulated by ultraviolet light to produce various reactive oxygen species (ROS), such as hydroxyl radicals and superoxide anions. These reactive oxygen species can damage cells and are also related to melanoma and skin photoaging. However, when zinc oxide nanoparticles meet the characteristics of the present invention, their ability to produce various reactive oxygen species when stimulated by ultraviolet light is weakened.
[0018] Another aspect of the present invention is to provide a zinc oxide nanoparticle, wherein the nanoparticle has a core-shell structure consisting of a core and an outer shell layer, wherein the core comprises silicon dioxide nanoparticles, and the shell layer is zinc oxide.
[0019] Furthermore, the silicon dioxide is carboxyl-modified silicon dioxide.
[0020] Furthermore, when the zinc oxide nanoparticles of the present invention are dispersed in water, under ultraviolet light excitation for 5 seconds, the generation of singlet oxygen is less than 10%, preferably less than 8%, more preferably less than 7%, more preferably less than 6%, and more preferably less than 5%.
[0021] Furthermore, when the zinc oxide nanoparticles of the present invention are dispersed in water, under ultraviolet light excitation for 10 seconds, the generation of singlet oxygen is less than 16%, preferably less than 15%, more preferably less than 14%, more preferably less than 13%, and more preferably less than 12%.
[0022] Furthermore, zinc oxide nanoparticles were dispersed in water at a concentration of 0.2 mg / ml, and the singlet oxygen generation ratio was measured.
[0023] The calculation formula of the singlet oxygen is as follows: Singlet oxygen generation ratio = [Abs (400 nm,曝光0s) -Abs (400 nm,曝光时长) ] / Abs( 400 nm,曝光0s )×100% Abs refers to the absorbance of the sample in the ultraviolet region, namely, the UVA and UVB regions; Furthermore, when the zinc oxide nanoparticles are dispersed in water, the peak value (Abs) of the absorption peak of the spectrum in the wavelength range of 280-320 nm is greater than 0.2, preferably greater than 0.3, preferably greater than 0.4, preferably greater than 0.5, preferably greater than 0.6, preferably greater than 0.7, preferably greater than 0.8, preferably greater than 0.9, preferably greater than 1.0, preferably greater than 1.1, preferably greater than 1.2, preferably greater than 1.3, preferably greater than 1.4, preferably greater than 1.5.
[0024] Furthermore, zinc oxide nanoparticles were dispersed in water at a concentration of 0.2 mg / ml, and the spectrum was measured.
[0025] Furthermore, the zinc oxide nanoparticles of the present invention have a distribution of at least 100% or more, preferably at least 110% or more, preferably at least 120% or more, preferably at least 130% or more, preferably at least 140% or more, preferably at least 150% or more, preferably at least 200% or more, preferably at least 300% or more, preferably at least 400% or more, preferably at least 500% or more, preferably at least 600% or more, preferably at least 70% or more. 0% or more distribution, preferably having a distribution of at least 800% or more, preferably having a distribution of at least 900% or more, preferably having a distribution of at least 1000% or more, preferably having a distribution of at least 1100% or more, preferably having a distribution of at least 1200% or more, preferably having a distribution of at least 1300% or more, preferably having a distribution of at least 1400% or more, preferably having a distribution of at least 1500% or more, preferably having a distribution of at least 1600% or more, preferably having a distribution of at least 1700% or more, preferably having a distribution of at least 1800% or more, preferably having a distribution of at least 1900% or more, preferably having a distribution of at least 2000% or more.
[0026] Further, when the nanoparticles are dispersed in water, they may optionally have an average hydrated particle size or / and PDI or / and D10 or / and D50 or / and D90 or / and Zeta potential or / and TEM particle size or / and average hydrated particle size / (TEM a +TEM b ).
[0027] Another aspect of the present invention is to provide a zinc oxide nanoparticle, wherein the nanoparticle has a core-shell structure consisting of a core and an outer shell layer, wherein the core of the nanoparticle is composed of carboxyl-modified silicon dioxide (SiO 2 -COOH) was prepared; Further, the shell layer is zinc oxide; Further, in the nanoparticles, the mass ratio of zinc to silicon is 100:1 to 5000:1, or 200:1 to 5000:1, or 300:1 to 5000:1, or 400:1 to 5000:1, or 500:1 to 5000:1, or 500:1 to 4900:1, or 500:1 to 4800:1, or 500:1 to 4700:1, or 500:1 to 4600:1, or 500:1 to 4500:1, or 500:1~4400:1, or 500:1~4300:1, or 500:1~4200:1, or 500:1~4100:1, or 500:1~4000:1, or 500:1~3500:1, or 500:1~3000:1, or 500:1~2500:1, or 1000:1~3000:1, or 1500:1~3000:1, or 200 0:1~3000:1, or 2100:1~3000:1, or 2200:1~3000:1, or 2300:1~3000:1, or 2400:1~3000:1, or 2500:1~3000:1, or 600:1~5000:1, or 700:1~5000:1, or 800:1~5000:1, or 900:1~5000:1, or 1000:1~500 0:1, or 1100:1~5000:1, or 1200:1~5000:1, or 1300:1~5000:1, or 1400:1~5000:1, or 1500:1~5000:1, or 1600:1~5000:1, or 1700:1~5000:1, or 1800:1~5000:1, or 1900:1~5000:1, or 2000:1~5000:1.
[0028] Furthermore, in the nanoparticles, the mass ratio of zinc to silicon is 100:1-1000:1, or 200:1-900:1, or 300:1-800:1, or 300:1-700:1, or 300:1-600:1, or 300:1-500:1, or 300:1-400:1.
[0029] Furthermore, the mass ratio of zinc to silicon in the nanoparticles is obtained by TEM / EDS.
[0030] Further, when the nanoparticles are dispersed in water, they optionally have an average hydrated particle size or / and PDI or / and D10 or / and D50 or / and D90 or / and Zeta potential or / and TEM particle size or / and average hydrated particle size / (TEM a +TEM b ).
[0031] The present invention also provides use of the zinc oxide nanoparticles in preparing sunscreen cosmetics.
[0032] The present invention also provides a dispersion, comprising the zinc oxide nanoparticles and an adjuvant acceptable in cosmetics. The zinc oxide nanoparticles have the characteristics as defined above. Before being formulated into cosmetic preparations, the nanoparticles can be stored in the form of a dispersion for the convenience of storage and sale. In order to prevent the nanoparticles from agglomerating during storage and / or to accelerate the dispersion of the nanoparticles in the dispersion in the cosmetics during the production of cosmetics, a surfactant or other functional adjuvant can be added to the dispersion, such as a functional adjuvant that prevents the particles from agglomerating and increases stability, or an adjuvant for color adjustment.
[0033] The present invention also provides a use of the dispersion for preparing sunscreen cosmetics.
[0034] The invention provides a cosmetic comprising the zinc oxide nanoparticles or the object to be dispersed.
[0035] The invention provides a cosmetic prepared from the to-be-dispersed substance.
[0036] The present invention provides a method for preparing the zinc oxide nanoparticles, comprising the following steps: Step 1: adding a zinc source into a solvent to form a uniform dispersion 1; uniformly dispersing a nucleating agent into water to form a dispersion 2; Step 2: mixing dispersion 1 and dispersion 2, wherein the mass ratio of the nucleating agent to the zinc source in the obtained mixture is 0.15:100-2000; Step 3: heating the mixture to 120-140° C. and stirring; preferably, stirring for not less than 10 min; Step 4: Continue to raise the temperature to 140-200°C until the reaction is complete; preferably, the reaction time is not less than 90 minutes; Step 5: After the reaction liquid is cooled to room temperature, the solid-liquid separation is performed, and the solid is separated by washing three times; Step 6: After the solid is dried, it is crushed with a powder grinder to obtain zinc oxide nanoparticles; The nucleating agent is carboxyl-modified silica nanoparticles.
[0037] Preferably, the concentration of the zinc source in the dispersion 1 is 0.5-2 mol / L, or 0.6-1.9 mol / L, or 0.7-1.8 mol / L, or 0.8-1.7 mol / L, or 0.9-1.6 mol / L, or 1-1.5 mol / L, or 1-1.4 mol / L, or 1-1.3 mol / L, or 1-1.2 mol / L, or 1-1.1 mol / L, or 0.5-1.5 mol / L, or 0.6-1.4 mol / L, or 0.7-1.3 mol / L, or 0.8-1.2 mol / L, or 0.9-1.1 mol / L.
[0038] Preferably, the concentration of the nucleating agent in the dispersion 2 is 10% to 20% by mass, or 11% to 20%, or 12% to 20%, or 13% to 20%, or 14% to 20%, or 15% to 20%.
[0039] Preferably, the mass ratio of the nucleating agent to the zinc source in the mixture is 0.15:100~2000; or 0.15:100~1000, or 0.15:100~800, or 0.15:200~800, or 0.15:300~800, or 0.15:400~800, or 0.15:500~800, or 0.15:500~700, or 0.15:500~600, or 0.15:100~700, or 0.15:100~600, or 0.15:100~500.
[0040] Preferably, the zinc source is added to the solvent to form a uniform dispersion with a concentration of 0.5 to 5 mol / L, preferably 0.5 to 4 mol / L, preferably 0.5 to 3 mol / L, preferably 0.5 to 2 mol / L, and preferably 1 ± 0.5 mol / L.
[0041] Preferably, the zinc source is selected from one or more of zinc acetate, zinc nitrate, zinc chloride, zinc sulfate, and zinc ethylhexanoate.
[0042] Preferably, the zinc source is selected from zinc acetate.
[0043] Preferably, the solvent is selected from glycol solvents.
[0044] Preferably, the solvent is selected from one or more of ethylene glycol, diethylene glycol (DEG), tetraethylene glycol (TEG), polyethylene glycol 200 (PEG200), polyethylene glycol 300 (PEG300), and polyethylene glycol 400 (PEG400).
[0045] Preferably, the solvent is selected from tetraethylene glycol.
[0046] Preferably, in step 4, the temperature is raised to 160-200° C. Preferably, the temperature is raised to 170-190° C. Preferably, the temperature is raised to 180±5° C.
[0047] Another aspect of the present invention is to provide a silicon dioxide for preparing zinc oxide nanoparticles, specifically carboxyl-modified silicon dioxide (SiO 2 -COOH) nanoparticles, the average hydrated particle size of the carboxyl-modified silica nanoparticles ranges from 10 to 50 nm, the PDI is not greater than 0.05, and the zeta potential is greater than -40 mV. Preferably, the zeta potential is greater than -41 mV, or greater than -42 mV, or greater than -43 mV, or greater than -44 mV, or greater than -45 mV, or greater than -46 mV, or greater than -47 mV, or greater than -48 mV. Preferably, the PDI is not greater than 0.04, preferably, the PDI is not greater than 0.03, and preferably, the PDI is not greater than 0.02.
[0048] Another aspect of the present invention is to provide a carboxyl-modified silica (SiO 2 -COOH) nanoparticles for preparing zinc oxide nanoparticles.
[0049] Furthermore, the carboxyl-modified silica (SiO 2 -COOH) nanoparticles are used to prepare sunscreen nanoparticles, and it serves as a nucleating agent for the nanoparticles.
[0050] Furthermore, the carboxyl-modified silica (SiO 2 -COOH) nanoparticles are used to prepare sunscreen nanoparticles. The prepared sunscreen nanoparticles have a core-shell structure consisting of a core and a shell. The core is composed of carboxyl-modified silica nanoparticles (SiO 2 -COOH) with a shell of zinc oxide.
[0051] Furthermore, another aspect of the present invention is to provide a carboxyl-modified silica (SiO 2 -COOH) preparation method: Step 1: dispersing silicon dioxide in water to form a suspension; Step 2: Add 3-aminopropyltriethoxysilane (APTES) to the above SiO 2 The suspension was stirred and reacted to obtain amino-modified silica (SiO 2 -NH 2 ); Step 3: centrifuging the mixed solution obtained in step 2, washing and separating the precipitate and drying it; Step 4: Disperse the solid obtained in step 3 in DMF, add succinic anhydride and stir to react; Step 5: Centrifuge the mixed solution obtained in step 4, wash and separate the precipitate, and dry it to obtain carboxyl-modified silica (SiO 2 -COOH).
[0052] Preferably, the prepared SiO 2 -COOH has the above-mentioned characteristic range.
[0053] Preferably, the silicon dioxide nanoparticles are prepared according to the following method: Step 1: Dissolve arginine in water, then add cyclohexane and tetraethyl silicate (TEOS) and mix well; Step 2: The mixed solution is placed under high temperature to react and finally obtain silica nanoparticles (SiO 2 ); Preferably, the average hydrated particle size of the silicon dioxide nanoparticles is in the range of 10 to 50 nm, the PDI is not greater than 0.05, and the zeta potential is greater than -20 mV. For example, the zeta potential may be -25 mV, -30 mV, or -31 mV.
[0054] Preferably, the average hydrated particle size of the silica nanoparticles is in the range of 10 to 50 nm, the PDI is not greater than 0.05, and the zeta potential is greater than -31 mV. Preferably, the PDI is not greater than 0.04, preferably, the PDI is not greater than 0.03, and preferably, the PDI is not greater than 0.02.
[0055] Another aspect of the present invention is to provide a method for preparing zinc oxide nanoparticles. The following steps are involved: Step 1: Adding a zinc source into a solvent to form a uniform dispersion; Step 2: uniformly dispersing the nucleating agent into the above dispersion; finally, the mass ratio of the nucleating agent to the zinc source in the obtained mixture is 0.15:100-2000; Step 3: Heat the mixture to 120-140°C and stir; Step 4: Continue to raise the temperature to 140-200°C until the reaction is complete; Step 5: After the reaction liquid is cooled to room temperature, solid-liquid separation is performed, and solid is obtained by washing and separation; Step 6: After the solid is dried, it is crushed with a powder grinder to obtain zinc oxide nanoparticles; The nucleating agent is carboxyl-modified silica nanoparticles.
[0056] Furthermore, in the preparation method as described above, the zinc source is selected from one or more of zinc acetate, zinc nitrate, zinc chloride, zinc sulfate, and zinc ethylhexanoate.
[0057] Furthermore, in the preparation method as described above, the solvent is selected from a diol solvent.
[0058] Furthermore, in the preparation method as described above, in step 2, the mass ratio of the nucleating agent to the zinc source is 0.15:100~1000; or the mass ratio is 0.15:100~800, or the mass ratio is 0.15:200~800, or the mass ratio is 0.15:300~800, or the mass ratio is 0.15:400~800, or the mass ratio is 0.15:500~800.
[0059] Furthermore, in the preparation method as described above, in step 4, the temperature is raised to 160-200°C; or raised to 170-190°C; or raised to 180±5°C.
[0060] Furthermore, the feeding ratio of the core (nucleating agent) and the shell (zinc source) material of the nanoparticles is 0.15:100-2000 in terms of mass ratio; or 0.15:100-1000, or 0.15:100-800, or 0.15:200-800, or 0.15:300-800, or 0.15:400-800, or 0.15:500-800, or 0.15:500-700, or 0.15:500-600, or 0.15:100-700, or 0.15:100-600, or 0.15:100-500.
[0061] Related terms: Silicon dioxide: The silicon dioxide in the zinc oxide nanoparticles of the present invention may be unmodified or modified with other functional groups. The modified groups are preferably capable of ionizing in the reaction environment to generate negative charges, such as carboxyl groups, for enhancing zinc ion adsorption. Or other groups that cannot be ionized but have electronegativity.
[0062] Hydrated particle size: refers to the diameter of a substance in fluid dynamics. The hydrated particle size of a substance can be measured by a dynamic light scattering instrument. The test principle is based on the scattering of light by particles, which is well known to those skilled in the art.
[0063] Average hydrated particle size: refers to the weighted average of the particle sizes of each particle. In the present invention, the average hydrated particle size refers to the average value obtained by weighted averaging the number of particles corresponding to the hydrated particle size.
[0064] TEM particle size: TEM is a transmission electron microscope. The particle size calculated by Image J software on the particles in the TEM image is the TEM particle size.
[0065] TEMa: represents the minimum value of TEM particle size.
[0066] TEMb: indicates the maximum TEM particle size.
[0067] PDI: Polydispersity Index is one of the important parameters to characterize the uniformity of particle distribution. PDI is usually obtained by dynamic light scattering.
[0068] Span: Particle size distribution width (Span) is another indicator that characterizes the width of particle distribution. Span is usually used to characterize asymmetric particle distribution systems, especially when the particle diameter distribution is highly skewed. The calculation formula for Span is: Span = (D90-D10) / D50.
[0069] D10: The particle size corresponding to when the cumulative particle size distribution percentage of the test sample reaches 10%, which can be obtained by dynamic light scattering.
[0070] D50: The particle size corresponding to when the cumulative particle size distribution percentage of the test sample reaches 50%, which can be obtained by dynamic light scattering.
[0071] D90: The particle size corresponding to when the cumulative particle size distribution percentage of the test sample reaches 90%, which can be obtained by dynamic light scattering.
[0072] Zeta potential: used as a measure of the strength of mutual repulsion or attraction between particles, which can be obtained by dynamic light scattering. For potential values, the "-" before the value represents a negative potential. Therefore, when comparing the potential size, only the absolute value is considered, and the influence of "-" on the value size is not considered.
[0073] Any of the zinc oxide nanoparticles defined above in the present invention has the following technical effects when used in sunscreen products: 1. Good dispersibility in water: For particles that are easy to aggregate, they need to be dispersed in cosmetic formulas with poor fluidity to avoid aggregation and formation of lumps, which will cause adverse effects such as false white that affect the appearance. For this reason, if water is used as the main dispersion carrier, a thickener is often added to reduce the fluidity of its particles (increase viscosity) to avoid aggregation. However, adding too much thickener will cause problems such as feeling greasy after use and poor air permeability. The zinc oxide nanoparticles prepared by the present invention are well dispersed in water, and the viscosity requirements of the dispersion carrier of cosmetics are low, thereby reducing the amount of such thickeners used, improving the comfort of users, and reducing the probability of false white.
[0074] 2. Less strong oxidizing substances are produced: The nanoparticles of the present invention and the sunscreen composition prepared therefrom not only have stronger ultraviolet absorption ability, but also produce less strong oxidizing substances. For example, the proportion of singlet oxygen generated at 10s is preferably less than 17%, more preferably less than 16%, more preferably less than 15%, more preferably less than 14%, more preferably less than 13%, more preferably less than 12%, and more preferably less than 11%. This means that when the same sunscreen effect is achieved, if the zinc oxide nanoparticles of the present invention are used, the amount used will be reduced, or the use of chemical sunscreen agents will be reduced or even eliminated. In addition, since less strong oxidizing agents are produced, the amount or type of reducing chemical agents used can also be reduced. Some users are sensitive to the use of these chemical agents, and sometimes even uncomfortable. Reducing the amount or type of these chemical agents can make it easier to obtain a mild formula, which can be suitable for more people and is also simpler for preparing cosmetics.
[0075] 3. More delicate skin: Due to the good dispersion effect of the invention, the agglomeration phenomenon is reduced, the particle feel is more delicate, and the comfort of use is improved.
[0076] 4. Good sunscreen effect: The absorbance (Abs) of the nanoparticles of the present invention to ultraviolet light is preferably greater than 0.5, more preferably greater than 0.6, more preferably greater than 0.7, more preferably greater than 0.8, more preferably greater than 0.9, and more preferably greater than 1.0. It shows stronger ultraviolet spectrum absorption performance and greatly improves the sunscreen effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0077] Figure 1 is a particle size distribution diagram of silicon dioxide nanoparticles in Example 1; Figure 2 is a TEM image of the silicon dioxide nanoparticles in Example 1; Figure 3 is a particle size distribution diagram of carboxyl-modified silica nanoparticles in Example 1; Figure 4 TEM image of carboxyl-modified silica nanoparticles in Example 1; Figure 5 This is a TEM image of zinc oxide nanoparticles prepared in Comparative Example 1 dispersed in water; Figure 6 This is a TEM image of zinc oxide nanoparticles prepared in Example 2 dispersed in water; Figure 7 This is a TEM image of zinc oxide nanoparticles prepared in Example 3 dispersed in water; Figure 8 This is a TEM image of zinc oxide nanoparticles prepared in Example 4 dispersed in water; Fig. 9This is a TEM image of zinc oxide nanoparticles prepared in Comparative Example 2 dispersed in water; Fig.10 This is a TEM image of zinc oxide nanoparticles prepared in Comparative Example 3 dispersed in water; Fig.11 This is a TEM image of zinc oxide nanoparticles prepared in Example 5 dispersed in water; Fig.12 This is a TEM image of zinc oxide nanoparticles prepared in Example 6 dispersed in water; Fig.13 This is a TEM image of zinc oxide nanoparticles separated from Pavise dispersed in water in Comparative Example 4; Fig.14 The absorption spectrum was obtained by testing with an ultraviolet visible spectrophotometer (TU-1810). In the figure, "0.15-10-0.02%", "0.15-100-0.02%", "0.15-500-0.02%", "0.15-800-0.02%", and "0.15-2000-0.02%" respectively indicate that the tested samples were prepared according to a mass ratio of nucleating agent to zinc source of 0.15:10 (Comparative Example 1), 0.15:100 (Example 2), 0.15:500 (Example 3), 0.15:800 (Example 4), and 0.15:2000 (Comparative Example 2), and were uniformly dispersed in water at a concentration of 0.2 mg / ml. "Pavise-0.02%" indicates zinc oxide nanoparticles separated from Pavise (Comparative Example 4), which were uniformly dispersed in water at a concentration of 0.2 mg / ml. Fig.15 The absorption spectra were obtained by testing with a UV-visible spectrophotometer (TU-1810). In the figure, "140°C-0.02%", "160°C-0.02%", "180°C-0.02%" and "200°C-0.02%" respectively indicate that the tested samples are from Comparative Example 3, Example 5, Example 3 and Example 6, and are uniformly dispersed in water at a concentration of 0.2 mg / ml. DETAILED DESCRIPTION
[0078] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0079] Unless otherwise specified, the materials and reagents used in the following examples are all common commercial products and can be purchased on the market.
[0080] The present invention will be further described below by way of examples, which are not intended to further limit the present invention. It should be understood by those skilled in the art that equivalent replacements or corresponding improvements made to the present invention still fall within the scope of protection of the present invention.
[0081] Example 1 Carboxyl-modified silica nanoparticles (SiO 2 Preparation of -COOH): Step 1: Dissolve 9.1 mg of arginine in 6.9 mL of deionized water, then add 0.45 mL of cyclohexane and 0.55 mL of tetraethyl orthosilicate (TEOS) and mix well. Step 2: The mixed solution was placed at 60°C and stirred continuously for 20 h to obtain silica nanoparticles (SiO 2 ); Step 3: Add 0.5 mL of 3-aminopropyltriethoxysilane (APTES) to the above SiO 2 The suspension was stirred at room temperature overnight to obtain amino-modified SiO 2 (SiO 2 -NH 2 ); Step 4: Centrifuge the mixture and wash the lower precipitate with ethanol, N,N -Dimethylformamide (DMF) washing; Step 5: Take 60 mg of the precipitate and resuspend it in DMF, add 100 mg of succinic anhydride and stir at room temperature overnight; Step 6: The mixed solution was centrifuged, and the lower precipitate was washed with DMF and deionized water respectively, and the precipitate was dried to obtain carboxyl-modified SiO 2 (SiO 2 -COOH).
[0082] The zeta potential of silica nanoparticles was -31.2 mV, and the zeta potential of carboxyl-modified silica nanoparticles was -47.9 mV, which shows that the silica was successfully connected to carboxyl groups, thereby enhancing the electronegativity. In addition, the modification did not affect the particle size distribution (such as Figure 1~Figure 4 as shown).
[0083] Example 2 This embodiment provides a zinc oxide nanoparticle and a preparation method thereof, the preparation method comprising the following steps: Step 1: Disperse zinc acetate (zinc source) uniformly in tetraethylene glycol (solvent) to form mixture 1 (concentration is 1 mol / L).
[0084] Step 2: Carboxyl-modified silica nanoparticles (nucleating agent) are uniformly dispersed in water to form mixture 2 (mass fraction is 15%). Subsequently, mixture 1 is mixed with mixture 2, and the mass ratio of the nucleating agent to the zinc source in the obtained mixture is 0.15:100.
[0085] Step 3: Heat the mixture to 120-140°C and premix for 10-30 minutes.
[0086] Step 4: Continue to raise the temperature to about 180°C and react for 90 to 120 minutes before stopping.
[0087] Step 5: After the reaction liquid is cooled to room temperature, solid-liquid separation is performed, and the solid is separated by washing with water three times.
[0088] Step 6: After the solid is dried, it is crushed using a powder grinder to obtain zinc oxide nanoparticles.
[0089] The nanoparticles were dispersed in water to prepare the test sample with a concentration of about 0.16 mg / ml. The results were obtained by transmission electron microscopy (Hitachi, HT7800). Figure 6 , TEM images were analyzed using Image J software and the TEM particle size was obtained to be 30~70 nm.
[0090] Example 3 The implementation method is the same as Example 2, except that in step 2, the mass ratio of the nucleating agent to the zinc source in the mixture is 0.15:500.
[0091] TEM images Figure 7 , TEM particle size = 30~70 nm.
[0092] Example 4 The implementation method is the same as Example 2, except that in step 2, the mass ratio of the nucleating agent to the zinc source in the mixture is 0.15:800.
[0093] TEM images Figure 8 , TEM particle size = 30~60 nm.
[0094] Example 5 Same as Example 2, except that the temperature is raised to about 160° C. in step 4.
[0095] TEM images Fig.11 , TEM particle size = 25~55 nm.
[0096] Example 6 Same as Example 2, except that the temperature is raised to about 200° C. in step 4.
[0097] TEM images Fig.12 , TEM particle size = 30~80 nm.
[0098] Comparative Example 1 The implementation method is the same as Example 2, except that the mass ratio of the nucleating agent to the zinc source in the mixture in step 2 is 0.15:10.
[0099] TEM images Figure 5 , TEM particle size = 20~40 nm.
[0100] Comparative Example 2 The implementation method is the same as Example 2, except that in step 2, the mass ratio of the nucleating agent to the zinc source in the mixture is 0.15:2000.
[0101] TEM images Fig. 9 , TEM particle size = 30~80 nm.
[0102] Comparative Example 3 Same as Example 2, except that the temperature is raised to about 140° C. in step 4.
[0103] TEM images Fig.10 , TEM particle size = 15~40 nm.
[0104] Comparative Example 4 A commercially available sunscreen skin care product with the trade name of Pavise was purchased, and the zinc oxide nanoparticles therein were separated and obtained.
[0105] TEM images Fig.13 , TEM particle size = 40~60 nm.
[0106] Test Example 1 1.1 Hydration particle size test The particles prepared in the above examples and comparative examples were dispersed in water and tested using a dynamic light scattering instrument (Anton Paar, Litesizer 500), and the data shown in Table 1 were obtained.
[0107] Table 1
[0108] The average hydrated particle size in Table 1 is the number average hydrated particle size obtained by weighted average of the number of particles. PDI stands for dispersion index, which is used to describe the range of particle size distribution. D10, D50, and D90 represent the particle size values corresponding to the cumulative distribution percentage from small to large reaching 10%, 50%, and 90%, respectively.
[0109] 1.2 Dispersion (aggregation) test TEM images can be used to observe the particle size of individual particles in a dry state, and can also indirectly reflect the aggregation of particles when dispersed in water. In order to quantitatively characterize whether particles are aggregated, the applicant describes the dispersion of particles in water by combining hydrated particle size data with TEM particle size, and the results are shown in Table 2.
[0110] Table 2
[0111] TEMa and TEMb represent the minimum and maximum TEM particle sizes, respectively.
[0112] The dispersion is evaluated by TEM images. +++ indicates excellent dispersion with few aggregated particles. ++ indicates good dispersion with some aggregated particles. + indicates that the particles are poorly distributed in the TEM image but are not tightly aggregated. This indicates that the particles have poor distribution uniformity in the TEM image and form tight aggregates.
[0113] Although the zeta potential is usually used to describe the dispersion stability in the prior art, it cannot accurately reflect the severity of the aggregation between particles. Figure 8 (Example 4) and Fig.10 (Comparative Example 3) It can be found that the aggregation degree of Comparative Example 3 is significantly higher than that of Example 4, but the Zeta potential corresponding to Example 4 is lower than that of Comparative Example 3. Therefore, the applicant calculated the average hydrated particle size / (TEM a +TEM b )” means: the proportion of particles in the particles after they aggregate to form aggregates (the particle size exceeds the maximum individual particle size), which is used to describe the severity of particle aggregation. Among them, TEM a +TEM b It indicates the particle size of the smallest aggregation state in theory, that is, the particle size of the largest and smallest particles tightly aggregated. When the particle size after aggregation exceeds TEM a +TEM b The more particles there are, the more serious the aggregation is. a +TEM b When the particle size of the aggregate does not exceed the particle size of the largest and smallest particles tightly aggregated, it is considered to have a low degree of aggregation and is treated as a single particle.
[0114] According to Table 2, the more tightly aggregated particles there are, the larger the average hydrated particle size will be. When the aggregation phenomenon is more serious, the average hydrated particle size / (TEM a +TEM b )>1, and the value is larger. When the particles are well dispersed, the average hydrated particle size / (TEM a +TEM b )≤1.
[0115] Test Example 2 Characterization of singlet oxygen generation ability The nanoparticles of the above-mentioned embodiment and comparative example were uniformly dispersed in water to prepare a sample with a concentration of 0.2 mg / ml. The singlet oxygen generation ability was tested by the ABDA method. 1 ml of 100 μM ABDA solution was mixed with each sample to be tested, and the ultraviolet absorption spectrum was tested. The sample was excited with a 365 nm ultraviolet lamp for 5 s, tested, and then excited for 5 s and tested. The decrease of the characteristic absorption peak of ABDA at 400 nm was observed. The light source was 5 cm away from the liquid surface. Singlet oxygen generation ratio = [Abs (400 nm,曝光0s) -Abs (400 nm,曝光时长) ] / Abs( 400 nm,曝光0s )×100% Table 3 below shows the calculation results of the singlet oxygen generation ratio when the exposure time is 5s and 10s respectively. The smaller the value of the singlet oxygen generation ratio, the less strong oxidizing substances are generated.
[0116] Table 3
[0117] From the above data, we can see that the nano zinc oxide used in the commercial product pavise utilizes the nano diamond core to remove holes through internal oxidation or by capturing electrons in the conduction band of the shell (as described in CN116171146A), so that the singlet oxygen generation ratio at 10s reaches 17.89%. a +TEM b )≤1, and average hydrated particle size≤90nm) nanoparticles have a singlet oxygen generation rate of less than 14% at 10s, and some can even reach less than 10%, which means that the nanoparticles provided by the present invention produce less strong oxidizing substances. According to the mechanism of ZnO generating active oxygen, the higher the light absorbance, the more active oxygen should be generated. In order to comprehensively evaluate the performance of the nanoparticles of the present invention as sunscreen, the following spectral absorption performance characterization was performed.
[0118] Test Example 3 Spectral absorption performance Those skilled in the art can understand that the generation of peroxides comes from the absorption of light energy by nano zinc oxide. Therefore, this test example performs a spectral absorption test on the nanoparticles of the above embodiments and comparative examples to comprehensively evaluate the spectral absorption performance and the corresponding generation of peroxides.
[0119] The nanoparticles of the above examples and comparative examples were uniformly dispersed in water at a concentration of 0.2 mg / ml. The ultraviolet-visible spectrophotometer (TU-1810) was used for testing, with a test range of 290-800 nm. The test results are shown in the attached Fig.14 and attached Fig.15 .
[0120] According to the test results, in the ultraviolet region, i.e., the UVA and UVB regions, the particles with absorbance (Abs) less than 1.0 are: Example 2, Comparative Example 1, Comparative Example 3, Comparative Example 4, and the particles with absorbance (Abs) greater than or equal to 1.0 are: Examples 3 to 6, Comparative Example 2. Therefore, Examples 3 to 6 and Comparative Example 2 have strong sunscreen capabilities, especially Example 3, Example 5 and Comparative Example 2.
[0121] Combined with the ultraviolet absorption data, it is unexpectedly found that among Examples 2 to 6, Examples 3 to 6 with an average hydrated particle size of more than 50 nm have stronger absorption capacity for the ultraviolet spectrum. That is, when 50 nm ≤ average hydrated particle size ≤ 90 nm, and the particles are well dispersed (average hydrated particle size / (TEM a +TEM b )≤1), having stronger ultraviolet spectrum absorption ability, and producing less strong oxidizing substances. In contrast, the ultraviolet light absorption (Abs) of the nanoparticles used in PAVise is far less than that of Examples 3 to 6.
[0122] Furthermore, by comparing Examples 3 to 6 (the absorbance (Abs) in the ultraviolet region is greater than 1.0), it can be observed that when the PDI decreases (the particle size distribution is more uniform), the proportion of singlet oxygen generated at 10s is also reduced accordingly, that is, compared with Examples 5 and 6, Examples 3 and 4 have smaller PDI (PDI≤20%), more uniform distribution, and less amount of strongly oxidizing substances generated.
[0123] Having strong ultraviolet absorption ability while producing less strong oxidizing substances means that the content of chemical sunscreen agents can be reduced in sunscreen formulas, and reducing chemical agents can also be reduced. Since the content or ingredients of these chemical agents are reduced, it is easier to obtain a mild formula that can be suitable for more people.
Claims
1. A zinc oxide nanoparticle, characterized in that: The outer layer of the nanoparticles is zinc oxide; When the nanoparticles are dispersed in water, the average hydrated particle size is ≤90nm. Average hydrated particle size / (TEM a +TEM b )≤1, TEMa and TEMb represent the minimum and maximum TEM particle sizes, respectively.
2. The zinc oxide nanoparticles according to claim 1, characterized in that: The nanoparticles have a core-shell structure consisting of a core and an outer shell layer, wherein the core contains silicon dioxide and the shell layer is zinc oxide.
3. The zinc oxide nanoparticles according to claim 2, characterized in that: 50nm≤average hydrated particle size≤90nm, or 60nm≤average hydrated particle size≤90nm, or 70nm≤average hydrated particle size≤90nm, or 60nm≤average hydrated particle size≤85nm.
4. The zinc oxide nanoparticles according to claim 3, characterized in that: When the nanoparticles are dispersed in water, D50≤80nm, or D50≤79nm, or D50≤78nm, or D50≤77nm, or D50≤76nm, or D50≤75nm.
5. The zinc oxide nanoparticles according to claim 4, characterized in that: D90≤110nm, or D90≤109nm, or D90≤108nm, or D90≤107nm, or D90≤106nm, or D90≤105nm.
6. The zinc oxide nanoparticles according to claim 5, characterized in that: The polydispersity index PDI of the zinc oxide nanoparticles is ≤0.3, or ≤0.2, or ≤0.19, or ≤0.18, or ≤0.
17.
7. Use of the zinc oxide nanoparticles according to any one of claims 1 to 6 for preparing sunscreen cosmetics.
8. A dispersion to be dispersed, characterized in that: The invention comprises the zinc oxide nanoparticles according to any one of claims 1 to 6 and an auxiliary material acceptable in cosmetics.
9. Use of the dispersion according to claim 8 for preparing sunscreen cosmetics.
10. A cosmetic, characterized in that: The invention comprises the zinc oxide nanoparticles according to any one of claims 1 to 6 or the dispersion according to claim 8.
Citation Information
Patent Citations
Method for preparing composite nano particle of silicon dioxide coated with zinc oxide
CN101143974A
Preparation method of surface-carboxylation gold magnetic core shell nano-composite particles
CN107658086A
Preparation method of nano-zinc oxide
CN110577235A
Sunscreen cosmetic composition and preparation method thereof
CN113476320A
Spherical composite functional material for cosmetics and preparation method thereof
CN114177097A